Chronic pancreatitis: diagnosis and treatment. Issue 848 (June 1996) - Sidhu, S.; Tandon, R. K.
Abstract : Three-dimensional magnetic resonance cholangiopancreatography is currently the most exciting new imaging technique for chronic pancreatitis. Endoscopy-assisted duodenal intubation during the secretin-cholecystokinin test reduces intubation time in difficult cases. The NBT-para-amino benzoic acid test has been refined to enhance its discriminant power. The cholesteryl-[C13]octanoate breath test and the faecal elastase test are newer highly sensitive and specific tubeless tests. Pain in chronic pancreatitis continues to be a vexing therapeutic issue. Enzyme treatment continues despite criticism. Neurotensin is the new suspected mediator of the feedback mechanism, which is downregulated by enzyme therapy. Steroid ganglion block is an exciting therapeutic tool for pain relief. Endoscopic pancreatic sphincterotomy, Dormia basketing and pancreatic stenting in conjunction with extracorporeal shock wave lithotripsy should be performed early in chronic pancreatitis to prevent parenchymal atrophy with ensuing exocrine and endocrine pancreatic dysfunction. The modified Puestow's procedure preserves endocrine and exocrine pancreatic functions besides relieving pain. Closed loop insulin infusion allows superior management of pancreatic diabetes following near total pancreatectomy. The standardised incidence rate of pancreatic cancer is 16.5 in patients with alcoholic chronic pancreatitis and 100 for tropical chronic pancreatitis. Aggressive treatment protocols combining neo-adjuvant chemoradiation and intra-operative radiation with surgery are being used to improve the prognosis in this dismal complication of chronic pancreatitis.